2008
DOI: 10.1080/09540120701842837
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of an HIV voluntary counseling and testing program for pregnant women in Georgia

Abstract: From 2002 to 2005 the Elizabeth Glaser Pediatric AIDS Foundation prevention of mother-to-child transmission of HIV project operated in Georgia and was managed by the Maternal and Child Care Union. The project covered Tbilisi, the capital, and included 34 clinics that provide women's healthcare. Out of 35,385 pregnant women starting prenatal care in clinics involved in the project, 91% (32,262) had received HIV counseling and, among those counseled, 94% (30,330) were tested for HIV antibodies; 14 pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The effectiveness of POC diagnostics on patient outcomes, including improving access to diagnosis and treatment, has been demonstrated [5,6,24,42,43,44,45,46,47,48]. Increasing the accessibility of POC diagnostics to resource-limited settings with poor access to laboratory infrastructure is one of the global health priorities [49].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of POC diagnostics on patient outcomes, including improving access to diagnosis and treatment, has been demonstrated [5,6,24,42,43,44,45,46,47,48]. Increasing the accessibility of POC diagnostics to resource-limited settings with poor access to laboratory infrastructure is one of the global health priorities [49].…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that the HIV epidemic in Georgia remains largely concentrated around the IDU community. Of the almost 80,000 pregnant women screened for HIV in Georgia, 32 women were HIV infected,[40,41] 66% of whom had a documented connection with the IDU community. Given the potential for undocumented IDU, some of the remaining 11 women also may be connected to this high-risk community or represent further transmission of HIV into the general community.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported on HIV voluntary testing and counselling, where test analysis was performed in a laboratory (30). The impact of POC diagnostics on the target population, HIV-infected women, was not clearly defined in four studies (3134).…”
Section: Resultsmentioning
confidence: 99%